PENGARUH METODE STORYTELLING MEDIA VIDEO DONGENG ANIMASI DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV DI UPT SPF SDN KASSI - Sairatu, Eklevina; Supardi, R; Sabillah, Bellona Mardhatillah; Abustang, Perawati Bte (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the storytelling method, aided by animated video storytelling, on the speaking skills of fourth-grade students at the SPF Unit of Kassi Elementary School. This study used a quantitative approach with a preexperimental research type and a One Group Pretest-Posttest Design.The variables in this study consisted of the storytelling method, aided by animated video storytelling, as the independent variable (X), and students' speaking skills as the dependent variable (Y). The study population was all 21 fourth-grade students at the SPF Unit of Kassi Elementary School. The sample of 21 students was selected using a purposive sampling technique. Data collection was conducted through observation, testing, and documentation. Data were analyzed using descriptive and inferential statistical analysis using SPSS version 25.The results showed that teacher activity in implementing the storytelling method, aided by animated video storytelling, achieved an average score of 3.0, categorized as very good, while student activity achieved an average score of 3.0, categorized as good. The average score for students' speaking skills increased from 48.48 in the pretest to 84.73 in the posttest. The results of the normality test indicated that the data were normally distributed, while the results of the homogeneity test indicated that the data were homogeneous. The results of the hypothesis test using the Paired Sample t-Test obtained a significance value (Sig. 2-tailed) of 0.000 < 0.05. Therefore, H₀ is rejected and H₁ is accepted. Based on these research results, it can be concluded that the storytelling method assisted by animated video media has a significant effect on the speaking skills of fourth-grade students at the SPF UPT SDN Kassi.